Establishment of a large-scale oral disease registry (NDCS-ODR) in a national specialty center - John Rong Hao Tay; Gustavo G. Nascimento; Jasmine Sio Hong Ho; Narayanan Ragavendran; Bryan Wei Ren Yeo; Hanimi Reddy Kallam; Sean Shao Wei Lam; Marco A. Peres (PLoS ONE, 2026)
This study describes the establishment of the National Dental Centre Singapore Oral Disease Registry (NDCS-ODR), a large-scale, electronic health records registry designed to capture real-world data on oral diseases. The NDCS-ODR was developed to standardize and integrate oral health data within Singapore Health Services, the country’s largest healthcare cluster. Its development, governance, and data architecture are described, with an overview of individuals with oral diseases recorded in the registry. Data collection from 2013 to June 2025 has been completed. As of June 2025, the NDCS-ODR comprises 229,249 unique patients, with a mean (SD) age of 49.1 (19.5) years and an approximately equal sex distribution. Most were of Chinese ethnicity (77.6%), and Singapore citizens (92.5%). Clinical variables indicated substantial disease and treatment burden, with a mean of 7.9 (7.7) missing teeth, 4.8 (6.2) restored surfaces, and 2.8 (3.4) restored teeth per patient. Among 108,517 recorded periodontal diagnoses, Stage III periodontitis (2018 EFP/AAP Classification) and severe chronic periodontitis (1999 Classification of Periodontal Diseases and Conditions) were most common. The NDCS-ODR represents Singapore’s first large-scale, real-world oral disease registry embedded within a national specialty center, demonstrating the feasibility of leveraging electronic health record data for research and service evaluation.